(untitled) (Papeles, 2021)
During the twentieth century, the Metropolitan Area of Buenos Aires (AMBA) underwent a process of great territorial and demographic growth. In the framework of different migratory flows that arrived in the city, a wide and highly heterogeneous periphery was structured. Within this framework and from a comparative perspective, the present document examines the residential and urban dynamics of neighborhoods on the periphery of the AMBA with different relative locations regarding the central city. The modes of production of the residential space are addressed where social actors have been involved in different ways in the city production, especially in Villa Lugano and Quilmes. The present document uses data from the Space Mobility Survey (EME) carried out in the Urban Studies Area of the Gino Germani Research Institute (FSoc -UBA). By analyzing the collected data, the socioeconomic profiles and residential trajectories of the population are compared. In the metropolitan area, it is possible to identify different transition spaces, not only transition between the countryside and the city, but also between different peripheries (and centralities). We can recognize transitions within the peripheries according to their relative location, the characteristics of the settlement and the production mode of land and housing.